Legal Consequences of Calculating State Financial Losses by Prosecutors in Corruption Crimes based on Decision Number: 69 K/Pid.Sus/2013 - Sholeh, Achmad Rilyadi; Noerdajasakti, Setiawan (International Journal of Business, Law, and Education, 2024)
State losses due to corruption are certainly detrimental to the country's economy. However, law enforcement against corruption crimes must still go through applicable legal procedures. Prosecutors do not have rules that specifically allow them to calculate and determine state losses. The research used is normative juridical. The research approach used is through legislation and cases. Based on Decision Number: 69 K/Pid-Sus/2013, it shows that the legal consequences of the calculation of state losses carried out by the prosecutor are the non-fulfillment of the element of harm to state finances or the non-fulfillment of formal requirements in terms of calculating state losses because it is not based on the calculation of institutions that have the authority and competence related to this matter, namely BPK or BPKP. The prosecutor in this case has violated the principle of legal certainty because it is out of the corridor of the applicable positive law.